Will they swim or sink? parental perception of water safety among their children - Farizan, Noor Hamzani; Sutan, Rosnah; K. C. Mani @ Subramanian, Kulanthayan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The magnitude of drowning as one of the leading causes of death among children in Malaysia may have been underestimated. Little is known on the level of awareness on water safety among parents as it might be associated with appropriateness and adequacy of the supervision. This study aims to describe perceptions of water safety among parents of primary school children. Methods: A cross-sectional survey with 719 respondent conducted to obtain information on parents self-reported on their children’s water-involved activity and swimming ability, self-estimated ability to rescue their child and perceptions of the risk of drowning and water safety for their children. Results: The result revealed that about 21.6% of respondents did not perceive drowning as one of the unintentional injury leading causes of death among children. Parents reported that their children had experienced a near- drowning incident (16.1%), and only 12.2% of the child had attended a formal swimming lesson. Majority of the parents did not involve in any water safety program (98.7%), can’t swim (61.6%), not been certified in CPR (87.3%) and not confident (87.3%) to perform resuscitation (CPR). Respondents also perceived their children could swim (42.1%), and they felt confident when their child in the water (45.6%). There were statistical differences between parents who reported their child had a near-drowning experience with their perception of children’s swimming ability. Conclusion: An exploration of parent’s perception of water safety provided an overview of the need for promoting awareness on drowning risk and water safety education in this country.